PEMBERDAYAAN PELAKU UMKM DIGITAL MELALUI STRATEGI OMNICHANNEL, BRANDING, DAN MANAJEMEN PELANGGAN - Bahdin Nur Tanjung; Parlaban Karo-Karo; Resi Lasmaria Naibaho (Nusantara Hasana Journal, 2025)
This Community Service Program aims to improve the marketing and sales performance of digital SMEs by strengthening omnichannel strategies, branding, and customer relationship management (CRM). Common issues include sales channels operating in isolation (WhatsApp–marketplaces–Instagram/TikTok), inconsistent brand messaging, unplanned content, slow customer response times, and a lack of documented customer and transaction data for retention purposes. Interventions are carried out through baseline assessments, practice-based training, channel optimization clinics, implementation of customer service SOPs, and mentoring to run 30–60-day omnichannel campaigns. Outputs include channel and customer journey maps, brand identity guidelines, content calendars, service script templates, a simple CRM dashboard, and KPIs monitored during the mentoring period.